2017
DOI: 10.1021/acsami.7b17002
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Oxidation of Chlorine-Doped Co(OH)2 Nanosheet Arrays on Carbon Cloth as a Bifunctional Oxygen Electrode

Abstract: The primary challenge of developing clean energy conversion/storage systems is to exploit an efficient bifunctional electrocatalyst both for oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) with low cost and good durability. Here, we synthesized chlorine-doped Co(OH) in situ grown on carbon cloth (Cl-doped Co(OH)) as an integrated electrode by a facial electrodeposition method. The anodic potential was then applied to the Cl-doped Co(OH) in an alkaline solution to remove chlorine atoms (elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
53
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(58 citation statements)
references
References 46 publications
5
53
0
Order By: Relevance
“…The other two intense satellite peaks at 786.0 eV and 803.2 eV were attributed to shake up excitation of the high‐spin Co 2+ ions in the sample . The binding energy difference between the two main peaks (Δ=16.1 eV) indicated that Co existed in the form of Co(OH) 2 , which was consistent with previous studies …”
Section: Resultssupporting
confidence: 90%
“…The other two intense satellite peaks at 786.0 eV and 803.2 eV were attributed to shake up excitation of the high‐spin Co 2+ ions in the sample . The binding energy difference between the two main peaks (Δ=16.1 eV) indicated that Co existed in the form of Co(OH) 2 , which was consistent with previous studies …”
Section: Resultssupporting
confidence: 90%
“…[8] For example, the large interlayer spacing and nanosheet (NS) structure of Co(OH) 2 are conducive to facilitate ion transport and provide large active area, respectively, which is vital to accelerate the OER kinetics in alkaline electrolytes. [9] However, Co(OH) 2 NS working as the anode catalyst of water electrolysis still cannot achieve ideal overpotential (lower than 300 mV at 10 mA cm À2 ), [10] indicating that the intrinsic activity of catalytic sites in Co(OH) 2 NS is limited. Consequently, it is critical to improve the catalytic efficiency and decrease the overpotential of Co(OH) 2 NS by engineering the surface atomic and electronic structures.Integrating metal nanoparticles with transition-metal compounds has been explored as a promising strategy to synthesize highly efficient electrocatalysts.…”
mentioning
confidence: 99%
“…As shown in Figure c, the C dl value is a linear slope of the plot, which is plotted by Δ J /2 (Δ J = J anodic − J cathodic ) at 0.95 V versus RHE versus scan rate . It is worth noting that the C dl value (8.46 mF cm −2 ) of CoFe@CNWs is much higher than those of Co@CNWs (3.56 mF cm −2 ) and Fe@CNWs (0.72 mF cm −2 ), suggesting that CoFe@CNWs possess larger electrochemically active area and more effective active sites for OER . Electrochemical impedance spectroscopy (EIS) is a powerful technique to characterize interfacial reactions and electrode kinetics in the OER process.…”
Section: Resultsmentioning
confidence: 86%
“…To date, the best electrocatalysts for HER and OER are platinum (Pt) and noble metal oxides (e.g., IrO 2 and RuO 2 ), respectively, which are normally scarce and expensive, leading to limitations in practicality . Moreover, most of other catalysts reported only have either HER or OER activity, which bring about additional cost during the synthesis of different materials . Hence, the current challenge is to develop a nonprecious, cost‐effective, and high‐stability electrocatalyst for both OER and HER as a potential alternative to noble metal‐based materials.…”
Section: Introductionmentioning
confidence: 99%